The utility of immature reticulocyte fraction as an indicator of erythropoietic response to altitude training in elite cyclists - Nadarajan, V.S.; Ooi, C.H.; Sthaneshwar, P.; Thompson, M.W. (Wiley-Blackwell Publishing, Inc, 2010)
P>Altitude training is sometimes employed by elite endurance athletes to improve their sea level performance. This improvement results from the increased red cell mass consequent upon the boost in erythropoietin (EPO) level that occurs as a response to the relatively hypoxic environment at high altitudes. We measured serum EPO levels together with various red cell and reticulocyte parameters including immature reticulocyte fraction (IRF) in eight national track-endurance cyclists, resident at sea-level, prior to and upon return from an altitude of approximately 1905 m. Reticulocytes and soluble transferrin receptor (sTfR) were significantly increased with reduction in ferritin levels immediately on return from high altitude indicating increased erythropoietic activity. IRF in particular showed a significant peak immediately on return but decline to sub-baseline levels by day 9, and recovery to baseline by day 16. Our results indicate that IRF is a sensitive marker of erythropoietic status in athletes undergoing altitude training and subsequent loss of EPO stimuli on return to sea level.